Menelusuri Jejak Rupa Wayang Klasik Bali - I Dewa Alit Dwija Putra (JURNAL RUPA, 2018)
The form of classical Balinese puppets through its long history, starting from primitive times, ancient Balinese, Balinese Hinduism, and colonialism until now. As a work of art of ancestral heritage with its various forms and developments, many Balinese people do not know the history of the puppet origins that became 'pakem' in its traditional art. To find out the traces of the classical puppets of Bali have similarities form with the depiction of puppets figures that exist in the temples of Central Java and East Java. The art crossed to Bali through the conquest of Bali during the Majapahit colonialism. This research uses historical method through heuristic stages, criticism, interpretation, and historiography, to be able to describe historically the origin of classical Balinese puppets as well as analysis matrix comparison to see the similarities and differences of Balinese puppets visual that exist in the temple the studies reliefs in the two areas. This research gives an idea that wayang art in Bali comes from Java which its early formation has been started since the time of Singosari kingdom and as a form of traditional artwork which is close to society which requirement of moral and spiritual value.